Acquired von Willebrand’s Syndrome during Autoimmune Disorder - Pizzuto, Javier; Ambriz, Raul; de la Paz Reyna, Maria; Monrroy, Luis M; Morales, Manuel R; Aviles, Agustin; Conte, Guillermo; Enriquez, Ruben (Thrombosis and Haemostasis, 1979)
A case with evidence of acquired von Willebrand’s syndrome associated with systemic lupus erythmatosus and Sjögren’s syndrome is described. The patient, who had no family history of bleeding, presented a haemorrhagic diathesis of recent origin, the bleeding time was prolonged, procoagulant Factor-VIII and von Willebrand factor levels were low and platelet aggregation was decreased with different concentrations of Ristocetin®.No improvement was seen after the tranfusion of cryoprecipitates, and there was no increase in procoagulant Factor-VIII.Clinical improvement resulted after treatment with corticosteroids, and later, the laboratory abnormalities characteristic of von Willebrand’s disease became normal. The level of procoagulant factor-VIII reached the very high level of 810%.